Sleep Deprivation, Cytokine Dysregulation, and the Risk of Cardiac Arrhythmia in Dogs - Adithya Sethumadhavan; Arun HS Kumar (Veterinary Medicine and Science, 2026)
ABSTRACT Background Sleep deprivation is increasingly recognised as a potent physiological stressor capable of altering immune function and promoting systemic inflammation. Emerging evidence suggests that these inflammatory changes may contribute to cardiac electrical instability and arrhythmia risk. However, the specific cytokines involved and their mechanistic pathways in canine models remain poorly characterised. This study aimed to (1) identify key cytokines consistently associated with sleep deprivation through a systematic review of the literature, and (2) perform a canine‐specific network and Gene Ontology enrichment analysis to characterise their interactions and potential mechanistic links to arrhythmogenesis. Methods A structured search of PubMed and Google Scholar identified 25 articles, of which 24 unique records were screened and seven met all inclusion criteria. From these studies, seven cytokines (IL‐6, IL‐17A, TNF, IL‐1, IL‐21, IFN‐γ, and CRP) were consistently associated with sleep deprivation and were subjected to canine‐specific protein–protein interaction analysis using the STRING database. Network topology and enriched biological processes were evaluated to identify mechanistic pathways connected to cardiac electrophysiology. Results Network analysis revealed several highly interconnected signalling nodes, including IL‐10, IL‐1β, JAK1, JAK2, IL‐6, STAT3, TNF, IFN‐γ, IL‐2, and IL‐4. Enrichment analysis indicated activation of processes such as chemokine production, positive regulation of osteoclast differentiation, JAK–STAT signalling, membrane protein ectodomain proteolysis, and regulation of vitamin D metabolism. Integration of primary and secondary networks revealed three major clusters cantered on interleukin signalling, TNF‐driven pathways, and CRP‐associated acute‐phase responses. Collectively, these pathways converge on cytokine‐mediated mechanisms known to influence myocardial conduction and increase arrhythmia susceptibility. Conclusions These findings indicate that sleep deprivation activates coordinated inflammatory networks that may predispose dogs to arrhythmias through multiple interconnected biological pathways. Therapeutic strategies addressing both inflammation and electrical instability may be required to fully manage arrhythmia risk in sleep‐deprived canine patients.